Pendidikan Kewirausahaan Nabi Muhammad Dan Implementasinya Di Rumah Tah}Fiz} Boarding School Yayasan Amanah Umat Mulia Yogyakarta Tahun 2015 - Sunardi, Sunardi; , Dr. Ari Anshori, M. Ag; , Dr. Sabar Narimo, MM, M.Pd (2015)
The first objective of the research is to describe The Prophet Muhammad entrepreneurship education and the second objective is to describe its implementation at Rumah Tahfiz Boarding School Yayasan Amanah Umat Mulia Yogyakarta. Prophet Muhammad was an entrepreneur and educator at once. He practiced entrepreneurship when he educated his companions to become entrepreneur. The term of entrepreneurship was not known at that time, but essentially had been taught and practiced. Rumah Tahfiz Boarding School Yayasan Amanah Umat Mulia Yogyakarta has a vision and mission to set an example of Prophet Muhammad in various sides. At this place, the researcher tried to analyze the implementation of entrepreneurship education of Prophet Muhammad. Through historical method, the researcher was able to get an idea of Prophet Muhammad ntrepreneurship education and its practice. By doing some observations and interviews, the researcher tried to collect some data which are relevant to the implementation of Prophet Muhammad entrepreneurship education at Rumah Tahfiz Boarding School Yayasan Amanah Umat Mulia Yogyakarta. Based on the results of descriptive analysis, it was revealed that Rumah Tahfiz Boarding School Yayasan Amanah Umat Mulia Yogyakarta has implemented entrepreneurship education of the Prophet Muhammad as a process, but hasn't given any visible result. Keywords: entrepreneurship, prophet Muhammad, implementing.